Exploring The Immunomodulation Profiles Of The Thp-1 Human Macrophage-derived Cell Line Mediated By Shigella Flexneri - Shabani, Nor Raihan Mohammad (2022)
Shigellosis is the primary cause of severe diarrhea, especially among children less than five years old. The occurrence of multi-drug resistant strains of Shigella species has contributed to the ineffectiveness of the existing treatment. Vaccination has become an essential requirement for preventing shigellosis. The invention of an epitope-based vaccine has directed the development of a new vaccine design model. Macrophages are specialized APCs that process antigens and then present the processed antigens to T-cells through HLA molecules. The immunomodulatory profiles of the macrophages infected by the clinical strains of S. flexneri 2a have remained undefined. THP-1-derived macrophages, as the model of human macrophages, were infected independently with mild and virulent strains of S. flexneri 2a at standard growth conditions. The gene expression level of inflammatory mediators was determined using qPCR, while NO production was measured using a commercial NO assay kit. The significant up-regulation of TNFα, IL-1β, IL-6, IL-12, iNOS, and NO indicates the pro-inflammatory reaction to S. flexneri 2a infection. The virulent strain also markedly increased the expression levels of the anti-inflammatory cytokine mRNAs. HLA class II gene expression was also investigated to extend the immunopeptidomics study and found the significant up-regulation of HLA class II by the Shigella-infected macrophages. LC-MS/MS-based immunopeptidomics strategy was employed to identify the peptides that can be used as potential candidates for the epitope-based Shigella vaccine development